Basophil Activation to Gluten and Non-Gluten Proteins in Wheat-Dependent Exercise-Induced Anaphylaxis - Gabler, Angelika Miriam; Gebhard, Julia; Norwig, Marie-Christin; Eberlein, Bernadette; Biedermann, Tilo; Brockow, Knut; Scherf, Katharina Anne (Frontiers in Allergy, 2022)
Wheat-dependent exercise-induced anaphylaxis (WDEIA) is a cofactor-induced wheat allergy. Gluten proteins, especially ω5-gliadins, are known as major allergens, but partially hydrolyzed wheat proteins (HWP) also play a role. Our study investigated the link between the molecular composition of gluten or HWP and allergenicity. Saline extracts of gluten (G), gluten with reduced content of ω5-gliadins (G-ω5), slightly (sHWP) and extensively treated HWP (eHWP) were prepared as allergen test solutions and their allergenicity assessed using skin prick test and basophil activation test (BAT) on twelve WDEIA patients and ten controls. Complementary SDS-PAGE, HPLC and MS analyses revealed that non-gluten proteins, mainly α-amylase/trypsin inhibitors (ATIs), were predominant in the allergen test solutions of G, G-ω5 and sHWP. Only eHWP contained gliadins and glutenins as major fraction. All allergen test solutions induced significantly higher %CD63+ basophils/anti-FcεRI ratios in patients compared to controls. BAT using sHWP yielded 100% sensitivity and 83% specificity at optimal cut-off and may be useful as another tool in WDEIA diagnosis. Our findings indicate that non-gluten proteins carrying yet unidentified allergenic epitopes appear to be relevant in WDEIA. Further research is needed to clarify the role of nutritional ATIs in WDEIA and identify specific mechanisms of immune activation.